Integrasi Pendekatan Tekstual dan Kontekstual terhadap Hadis Sahih di Era Modern - Ahmad Syauky; Nurmila Nurmila; Safrina Ariani (El Nubuwwah Jurnal Studi Hadis, 2025)
Understanding á¹£aá¸¥Ä«á¸¥ á¸¥adÄ«ths has remained a critical methodological discourse in both classical and contemporary Islamic studies. Two major hermeneutical approachesâ€”textual and contextualâ€”are central to this discourse. The textual approach emphasizes a literalist reading of the á¸¥adÄ«th text in order to preserve the authenticity and sanctity of the Prophet Muhammadâ€™s teachings. In contrast, the contextual approach considers the socio-historical and cultural background in which a á¸¥adÄ«th was transmitted, thereby enabling its normative messages to remain relevant to contemporary realities. This article addresses the methodological question of how these two interpretative approaches can be integrated to respond to the dynamic challenges of modern Muslim life.This study employs a qualitative-descriptive method using a library research model. The primary sources include both classical á¸¥adÄ«th compilations and contemporary scholarly literature. Selected á¹£aá¸¥Ä«á¸¥ á¸¥adÄ«ths that are often debated between textualist and contextualist interpretations are analyzed to demonstrate the theoretical implications of both approaches. Findings indicate that the textual and contextual approaches are not inherently contradictory but rather complementary. The textual method safeguards the transmissional integrity (riwÄyah) of the á¸¥adÄ«th, while the contextual approach ensures that its meanings (dirÄyah) can be appropriately situated within evolving socio-cultural frameworks. The integration of both provides a more balanced and comprehensive understanding of Prophetic traditions. In conclusion, a synthesis between textual fidelity and contextual relevance is essential to interpret á¸¥adÄ«ths holistically. This integrative framework is proposed as a viable model for contemporary á¸¥adÄ«th interpretation that is both normatively authentic and socially responsive.